Sistem Pendukung Keputusan Pemilihan Karyawan Baru dengan metode SAW (Simple Additive Weighting) Berbasis Web - Sindhu Rakasiwi; Intan Nurul Alfiani (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2021)
Performance is the result of work that can be achieved by a person or a group of people in an organization, in accordance with their respective authorities and responsibilities. Employee performance is very urgent and needs to be carried out in a planned, directed, and sustainable manner in order to improve capabilities and professionalism in public services. But on the other hand, the performance in public services has not been maximized in public services.The quality of employee work is still not visible in terms of accuracy and speed and the results of the work carried out are not in accordance with what is expected. As a reference material that can be used for comparison and a frame of reference for similar issues, so as to improve the quality of employees. And can be a reference and encouragement for employees as well as a measure of success in providing quality capabilities before engaging in other workforce competition.The goal to be achieved in this research is to find out how the performance of employees of PT. Proud of Indonesian Technology. This study uses the SAW methods, often also known as the weighted addition method. The basic concept of the SAW method is to find the weighted sum of the performance ratings for each alternative on all attributes. The SAW method requires the process of normalizing the decision matrix (X) to a scale that can be comparedThe results of the study show that there is a good response, it cannot be denied that the employee's performance has not been maximized. As well as inadequate facilities and infrastructure in the office which become an important aspect in influencing employee performance. The assessment process is still done manually and implemented in excel form, so it takes a long time to process data.